2020
DOI: 10.1186/s12886-020-01760-y
|View full text |Cite
|
Sign up to set email alerts
|

New PTEN mutation identified in a patient with rare bilateral choroidal ganglioneuroma

Abstract: Background Choroidal ganglioneuroma is an extremely rare tumor, and there is little knowledge regarding its pathogenesis. We aimed to investigate the phenotypic and genetic alterations in one sporadic patient with a rare case of bilateral choroidal ganglioneuroma. Methods A 6-year-old boy with histological diagnosis of bilateral ganglioneuroma was recruited for the study. Comprehensive ophthalmic examinations were performed. Genomic DNA was extract… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 34 publications
1
0
0
Order By: Relevance
“…PTEN encodes for the phosphatidylinositol-3,4,5-trisphosphate 3-phosphatase [35] and primarily dephosphorylates phosphoinositide substrates. It negatively regulates phosphatidylinositol-3,4,5-trisphosphate intracellular levels and functions as a tumor suppressor by negatively regulating the AKT/PKB signaling pathway [36]. In our study, we found that the overexpression of PIK3R1 and PIK3R4 was associated with a reduction in OS.…”
Section: Discussionsupporting
confidence: 51%
“…PTEN encodes for the phosphatidylinositol-3,4,5-trisphosphate 3-phosphatase [35] and primarily dephosphorylates phosphoinositide substrates. It negatively regulates phosphatidylinositol-3,4,5-trisphosphate intracellular levels and functions as a tumor suppressor by negatively regulating the AKT/PKB signaling pathway [36]. In our study, we found that the overexpression of PIK3R1 and PIK3R4 was associated with a reduction in OS.…”
Section: Discussionsupporting
confidence: 51%